Communication of teacher and students with and without Autistic spectrum disorder - Andressa Schmiedel; Cynthia Borges de Moura (Universidade Federal de Rondônia, 2018)
Purpose: compare the communicative profile between a teacher and students with and without Autism Spectrum Disorder (ASD). Method: two male subjects that regularly attend the 5th grade of elementary school, participated in the study. The communication between a teacher and a student diagnosed with ASD and another student without the Disorder was recorded, analyzed, and compared. The analysis was performed through the Pragmatic Protocol through communication clippings.  Results: The communication actions per minute prevailed in the case of the student without ASD, being the verbal communication the one most used by both students. Regarding the communicative functions, from the twenty analyzed ones, only three were used by both students during the communicative interaction with the teacher. Conclusion: Although the communicative action data prevailed in the communication of the student without ASD, generally, all other data indicated that the student with ASD displays a communicative interaction and that it is similar to the interaction of the student without the disorder.